Increased plasma carnitine levels in patients with liver cirrhosis - Yalvaç, Sema; Önal, Hasan; Aydın, Ahmet; Zeybek, Çiğdem A.; Baran, Ahmet; Kahveci, Arzu; Akın, Perihan; Özdemir, Sebati (Cerrahpaşa Medical Journal, 2019)
Objectives: Carnitine is an important essential cofactor in transfer of long chain fatty acids across the inner mitochondrial membrane. The aim of this study was to investigate total, free and acyl carnitine levels in patients with liver cirrhosis in comparison with healthy subjects. Methods: A total 55 (37 male / 18 female) cirrhotic patients were included in the study (33 compensated and 22 decompensated). 39 and 16 patients were associated with HBV and HCV, respectively. The control group consisted of 30 healthy persons. The statistical analyses were performed by student’s t test. Results: Total, free and acyl carnitine levels in all cirrhotic patients were higher than the control group’s levels (p<0.001). Moreover, all carnitine fractions of compensated cirrhosis were higher than control group’s levels and the levels of patients with decompansated cirrhosis (p<0.001 and p=0.005 respectively). Conclusion: Our results suggest that the increase in the plasma carnitine levels in patients with compensated and also decompansated liver cirrhosis can be due to result from competition of bile acids and bilirubin with tubular carnitine reabsorption and/or skeletal turnover.